Penyuluhan Kesehatan Masyarakat dengan Penyakit Hipertensi di Kelurahan Paledang Kota Bogor - Solehudin Solehudin; Emi Yuliza; Nur Eni Lestari; Nurul Ainul Shifa (PPNI UNIMMAN, 2025)
Community service is one of the pillars of the Tri Dharma of Higher Education which aims to provide real contributions to improving community welfare. In this context, the community service program implemented in RW 03, Paledang Village, Bogor City, aims to educate and intervene in health problems, especially hypertension. Hypertension was chosen based on the results of initial data analysis which showed the prevalence of high blood pressure reaching 66% in the community. Activities included hypertension gymnastics, health education, and melon juice distribution, which were carried out in a participatory manner by nursing students and supervising lecturers. The implementation method consisted of three stages: planning through data collection and analysis, implementation of educational and promotive activities, and evaluation to identify obstacles and impacts of the program. The results showed an almost even distribution between men and women, with the majority of respondents in the middle adult age group (40–59 years) and secondary education level (high school/vocational high school). These findings indicate that a community-based education and intervention approach can increase public awareness of the importance of preventing and controlling hypertension. This program has a positive impact, both for the community and students, through direct application of knowledge, improving public health, and strengthening the role of the nursing profession in the community.